INTEREST FREE BANKING IN TURKEY: A STUDY OF CUSTOMER SATISFACTION AND BANK SELECTION - H.Saduman Okumus; Elif Guneren Genc (European Scientific Journal, ESJ, 2013)
In the wakes of frequent episodes, interest free banking has been seen as an alternative to conventional banking rather than one component of financial system. Since its 1960s inception it has expanded worldwide with an excessive speed and its development has remained dynamic. In parallel with these developments, interest free banking in Turkey has grown rapidly with an annual growth of 35% in the last decade. The Participation Banks (PBs) operating in compliance with Islamic principles in Turkey has gained almost 6% market share. The expansion of interest free banking has also brought intensive competition between the PBs and conventional banks as well as among the PBs.The purpose of this study is to investigate customers’ awareness towards interest free products and services and determine their bank selection criteria and satisfaction towards financial products and services. Based on a sample of 281 respondents, it reveals that most of the respondents give the highest importance to religious belief as major factor for making selection of a bank to deal with. They recorded that they bank with conventional banks as well as PBs since the PBs do not have the products and services that are available them through the conventional banks. Based on our empirical findings; we also recorded a low level of customer satisfaction on the limited number of branches, the availability of a wide range of credits with favourable terms and high service commission and fees.